Azole-Resistance in Aspergillus terreus and Related Species: An Emerging Problem or a Rare Phenomenon? - Zoran, Tamara; Sartori, Bettina; Sappl, Laura; Aigner, Maria; Sánchez-Reus, Ferran; Rezusta, Antonio; Chowdhary, Anuradha; Taj-Aldeen, Saad J.; Arendrup, Maiken C.; Oliveri, Salvatore; Kontoyiannis, Dimitrios P.; Alastruey-Izquierdo, Ana; et al. (Frontiers in Microbiology, 2018)
Objectives: Invasive mold infections associated with Aspergillus species are a significant cause of mortality in immunocompromised patients. The most frequently occurring aetiological pathogens are members of the Aspergillus section Fumigati followed by members of the section Terrei. The frequency of Aspergillus terreus and related (cryptic) species in clinical specimens, as well as the percentage of azole-resistant strains remains to be studied. Methods: A global set (n = 498) of A. terreus and phenotypically related isolates was molecularly identified (beta-tubulin), tested for antifungal susceptibility against posaconazole, voriconazole, and itraconazole, and resistant phenotypes were correlated with point mutations in the cyp51A gene. Results: The majority of isolates was identified as A. terreus (86.8%), followed by A. citrinoterreus (8.4%), A. hortai (2.6%), A. alabamensis (1.6%), A. neoafricanus (0.2%), and A. floccosus (0.2%). One isolate failed to match a known Aspergillus sp., but was found most closely related to A. alabamensis. According to EUCAST clinical breakpoints azole resistance was detected in 5.4% of all tested isolates, 6.2% of A. terreus sensu stricto (s.s.) were posaconazole-resistant. Posaconazole resistance differed geographically and ranged from 0% in the Czech Republic, Greece, and Turkey to 13.7% in Germany. In contrast, azole resistance among cryptic species was rare 2 out of 66 isolates and was observed only in one A. citrinoterreus and one A. alabamensis isolate. The most affected amino acid position of the Cyp51A gene correlating with the posaconazole resistant phenotype was M217, which was found in the variation M217T and M217V. Conclusions:Aspergillus terreus was most prevalent, followed by A. citrinoterreus. Posaconazole was the most potent drug against A. terreus, but 5.4% of A. terreus sensu stricto showed resistance against this azole. In Austria, Germany, and the United Kingdom posaconazole-resistance in all A. terreus isolates was higher than 10%, resistance against voriconazole was rare and absent for itraconazole.